Othering Europe: Ambivalence in Moroccan Discourse Towards Modernity under the Dogmatic Understanding of Islam and the Political Affiliation to the Monarchy - Hamza Salih (European Scientific Journal, ESJ, 2021)
This paper is a study of the reaction of the Moroccan intellectual elite against/towards European modernity in the nineteenth century. The primary focus is on the Moroccan failure to formulate and develop a positive and reasonable response to European expansionism and menace. This threat may seem military in its core as it was related to colonialism, yet the encounter was essentially cultural and the reaction of the Moroccan elite took its grounds from religious and cultural stands. This is simply because Europe was not only a colonizing Other, but also a cultural opponent with which Morocco had armed conflicts, long-standing rivalries, and even cultural dialogues. This paper develops an argument that the Moroccan intellectual elite exemplified via ambassadorial travel writers, the Makhzen’s envoys to Europe, failed to see Europe as a possible model or at least to open some horizons of cultural dialogue and encounter. Due to cultural reasons and historical circumstances, this intellectual elite rejected Europe and modernity. The present paper limits itself to the question of ambivalence shown by Moroccan ambassadorial travel writers in their narratives. It argues that their travel accounts were torn between the writers’ religious thinking and political affiliations. It postulates that ambassadorial travel writers showed ambivalence in their connection to the idea of modernity. Their narratives were governed by the dichotomy of admiration of the material progress of Europe and rejection of Europe as a possible cultural model.